THE NEW STAGE OF ARTIFICIAL INTELLIGENCE: TOWARDS HUMAN-CENTERED INTELLIGENT SYSTEMS - Inobat G`aniyeva,; Ulasheva Shakhlo, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the emerging paradigm of human-centered artificial intelligence (AI), focusing on the development of intelligent systems that prioritize human values, ethics, and social well-being. As AI technologies advance, there is a growing need to design systems that not only enhance efficiency and automation but also respect human agency and ensure fairness, transparency, and accountability. The study examines the transition from data-driven and algorithm-centered AI to human-centered intelligent systems, where interdisciplinary collaboration and ethical governance play a crucial role. The research highlights practical examples in healthcare, education, and governance, where human-centered AI contributes to improved decision-making, inclusivity, and social trust.